Magnetic Measuring Instrument Based on Arduino Uno Microcontroller and its Implementation as A Learning Medium - Matsun Matsun; Boisandi Boisandi (Kappa Journal, 2024)
This study aims to develop a magnetic measuring instrument based on Arduino Uno microcontroller and apply the results as a learning medium to measure student achievement. This tool is designed to provide precise magnetic measurements using sensors integrated into the Arduino Uno. The measurement method implemented in this tool allows users to obtain magnetic data accurately and efficiently. This research is a Research and Development research using a five-stage ADDIE model. In preparation for the study, the analysis stage has been carried out. The Design, Development, and Implementation stages are carried out at the stage of research implementation. Evaluation is carried out at every stage starting from preparation, implementation to research reporting. The results of the research obtained based on the validation of material and media experts obtained an average value of 81 with a very feasible category so that the Arduino Uno microcontroller-based magnetic measuring instrument can be used in classroom learning. The results of the post test and pritest revealed that the Arduino Uno microcontroller-based magnetic measuring instrument proved effective in improving student learning outcomes with an N-Gain value of 0.76 in the high category. The implementation of this magnetic measuring instrument not only focuses on technical aspects, but also on its use as a learning medium. With a simple interface design and clear user guidance, the tool is expected to provide an interactive and effective learning experience. Users can understand the concept of magnetism and apply it in a practical context with the help of this tool. This research contributed to the development of magnetic measuring instruments that are affordable, easy to use, and can be applied in various learning contexts. Thus, the results of this research can be a reference for the development of similar technologies and provide benefits in the field of science and technology education.